The Quantity Theory of Money is Valid. The New Keynesians are Wrong! - Claude Hillinger; Bernd Süssmuth (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
We test the quantity theory of money (QTM) using a novel approach and a large new sample. We do not follow the usual approach of first differentiating the logarithm of the Cambridge equation to obtain an equation relating the growth rate of real GDP, the growth rate of money and inflation. These variables must then again be `integrated' by averaging in order to obtain stable relationships. Instead we suggest a much simpler procedure for testing directly the stability of the coefficient of the Cambridge equation. For 125 countries and post-war data we find the coefficient to be surprisingly stable. We do not select for high inflation episodes as was done in most empirical studies; inflation rates do not even appear in our data set. Much work supporting the QTM has been done by economic historians and at the University of Chicago by Milton Friedman and his associates. The QTM was a foundation stone of the monetarist revolution. Subsequently belief in it waned. The currently dominant New Keynesian School, implicitly or explicitly denies the validity of the QTM. We survey this history and argue that the QTM is valid and New Keynesians are wrong.
urn:nbn:de:bvb:19-epub-6987-8
Keywords: B22; E31; E41; E52; 330; new Keynesian theory; quantity theory of money; Quantitätstheorie; Schätzung; Welt